Dinamika Kewenangan Terhadap Perubahan Kebijakan Pemerintah Daerah Dalam Konteks Otonomi Daerah - Sambawa Ningrum, Herlina Ratna (Universitas Sang Bumi Ruwa Jurai, 2025)
This research analyses the dynamics of policy changes by local governments within the context of regional autonomy. The main focus of the study is on changes in authority and policy implementation that occur within a specific period. This case study enhances understanding of how regional autonomy influences the evolution of local government policies, and its impact on the relationship between local and central governments. The research method employs a qualitative approach with analysis of both primary and secondary data. Findings indicate that policy changes by local governments within the context of regional autonomy are often triggered by various factors, including political shifts, societal pressures, and external dynamics such as regulatory changes from the central government. Changes in authority also significantly impact decision-making processes and policy implementation at the local level. This research provides a significant contribution to understanding how regional autonomy affects the dynamics of local government policies, and its implications for decentralized governance systems